ANALYSIS OF FACTORS CAUSING THE EXISTENCE OF ILLEGAL PARKING ATTENDANTS AND PAK OGAH IN THE PERSPECTIVE OF SHARIA ECONOMICS IN MAJALENGKA DISTRICT - Bahari, Fauzi Rizky; Sutono; Rohmah, Nur; Awaliyah, Rika (P3M - STAI Kuningan, 2025)
The phenomenon of illegal parking attendants and pak ogah in the public spaces of Majalengka Regency reflects complex economic and social problems. This study aims to analyze the factors that cause the rampant practice and examine its suitability with the principles of Islamic economics. The research used descriptive qualitative methods with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that economic (unemployment and poverty), social (low education and permissive culture), and structural (weak regulations and lack of law enforcement) factors are the main causes. From an Islamic economic perspective, this practice contradicts the principles of justice, benefit and transparency of the contract. This study recommends solutions based on community empowerment through mosques and ZISWAF funds, strengthening integrated regulations, and sustainable Islamic economic education.